Let’s Put Arbitral Institutions to Compete: In Favor of the Award Scrutiny Process in Peru - Ezcurra Rivero, Huáscar (2020)
The enforceability of awards is the most valued feature of arbitration. This alternative dispute resolution mechanism depends, almost entirely, on the efficiency of the final product it provides: the award. The quality of this instrument, however, may vary depending on the arbitrators in charge of rendering it and, most important, the institutions that fulfill the function of regulating the arbitral procedure.In this article, the authors propose that arbitral institutions in Peru implement the scrutiny of awards in order to improve the quality and enforceability of awards. This scrutiny aims to be an additional competition factor among them as well as it leads them to having a higher quality standard in the services they offer. This measure is in accordance with the users’ preferences and would demand great institutional effort, a technical design work, a strong policy in favor of internationalization and a determined teaching work. Nevertheless, it would generate benefits that would far outweigh its costs for the practice of arbitration in the country and, most importantly, direct benefits for the users.